Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 4 - Applications of the Derivative - 4.9 Antiderivatives - 4.9 Exercises - Page 327: 18


$H(z) = z^{-6}$

Work Step by Step

$H(z)=-6z^{-7}$ $\int H(z)dz = \int -6z^{-7}$ $H(z) = \frac{-6z^{-7+1}}{-7+1}$ $H(z) = \frac{-6z^{-6}}{-6}$ $H(z) = z^{-6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.